(untitled) (Вісник: Міжнародні відносини, 2024)
This article tries to analyze the cooperation between the Russian state and the Russian Orthodox Church (ROC) from the past to the present. As it will be described below,in Russia, the state has almost everytime had domination over the church. Besides, the Russian Orthodox Church, throughout the history, formed the ideological pillars of Russia’s foreign policy, such as, Russian messianism. The church began to be used as a soft power of Moscow especially during the Second World War. Since then, the ROC has played a role of soft power in the foreign policy of the state. Since then, the US has been in cooperation with the Constantinople Patriarchate, while the Kremlin has backed the ROC. After the Soviet Union collapsed and especially after Vladimir Putin became the president of Russia, such cooperation between the state and the church intensified ever more. In the far abroad, the ROC helped the state to increase Russia’a influence in the Western world, while in the near abroad (in the post Soviet space), it played a role in reintegration of some of the ex-Soviet countries. However, especially after Russia’a annexation of Crimea, ie, after the Russian administration, instead of re-integration policy chose the policy of partition of Ukraine, implemenration of a “soft power” role became harder. Consequently, after the outbreak of the full scale invasion of Ukraine, ie, under the conditions of open invasion, the possibility to use the ROC as a soft power tool, decreased remarkably.